Marketing and Business Strategies for Coping with the Global Financial Crisis - Senthil Nathan, C. (Indian Journal of Marketing, 2010)
Global imbalance led to flood of money into U.S that kept interest rates low, inflated price of real estate, shares and assets. This can be considered to be the indirect cause of recession. This had allowed banks to develop structures and innovative products with higher returns. The products developed were so 'innovative' that risks associated with it could not be comprehended and inability to mitigate the risks led to today's most used jargon 'Global Financial Turmoil'. The authorities for controlling and regulating the bank activities in U.S had given their 'blessings' instead of intervening and preventing the calamity at right periods. Since the U.S is the 'mother' of all economies, the impact was felt by all countries including India. Thanks to prudent financial, monetary policies and balanced foreign investment ceiling on different industrial sectors, the impact of recession in India was less as compared to the other countries. With global experts and leaders working on a way out of the financial crisis, let us focus on strategies and tactics to negate and overcome the implications of 'Global financial Recession' on consumer behaviour and in markets.